Manajemen Pemerintah Dalam Penanganan dan Pengelolaan Sampah - Fitri Yanuar; Cucu Sugiarti; Haura Atthahara (Universitas Musamus, Merauke, Papua, 2020)
The market is a meeting place for sellers and buyers, marked by the interaction of buying and selling.Common problems that are often found in traditional markets are the accumulation of garbage, the smellof garbage around the market, and waste management by market managers who are considered notoptimal. The purpose of this study was to determine the management of handling and management ofwaste in Cibitung Main Market. This study uses a descriptive method with a qualitative approach. Thedata collection techniques used in this study were interviews, observation, documentation, andtriangulation. The results of this research on waste management and management in the Central Marketstill use conventional methods, namely collect - transport - throw away. The market manager does notyet have innovation and work progress in managing market waste. Even with the conventional methodwhich includes collect - transport - throw away, conditions in the field, garbage often piles up and isscattered in the market area and causes a strong odor. Another finding in the field is that there is onlyone TPS, whose load is not proportional to the volume of waste production which results in theaccumulation of garbage because it has exceeded the capacity limit and the smell of garbage is verystrong. While the thing that needs to be improved is to increase time for transporting waste, so that thegarbage does not accumulate too much.